2020
DOI: 10.3389/fimmu.2020.00514
|View full text |Cite
|
Sign up to set email alerts
|

Innate Activation of IFN-γ—iNOS Axis During Infection With Salmonella Represses the Ability of T Cells to Produce IL-2

Abstract: Pathogenic Salmonella serovars are a major cause of enteric illness in humans and animals, and produce clinical manifestations ranging from localized gastroenteritis to systemic disease. T cells are a critical component of immunity against this intracellular pathogen. The mechanisms by which Salmonella modulates T-cell-mediated immune responses in order to establish systemic infection are not completely understood. We show that infection of mice with Salmonella enterica serovar Typhimurium (S. Typhimurium) sup… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 56 publications
1
8
0
Order By: Relevance
“…Similar changes in cellularity have been previously reported in the peritoneal cavities and spleens of mice infected with pathogenic Salmonella and these have been associated with immunomodulatory roles in the establishment of infection with this pathogen [14][15][16].…”
Section: Mass Spectrometric Analysissupporting
confidence: 80%
“…Similar changes in cellularity have been previously reported in the peritoneal cavities and spleens of mice infected with pathogenic Salmonella and these have been associated with immunomodulatory roles in the establishment of infection with this pathogen [14][15][16].…”
Section: Mass Spectrometric Analysissupporting
confidence: 80%
“…In vivo infection in C57BL/6 mice suggested that STM Δ chiA mutant could not invade the PP, leading to an early fecal shedding, a lower bacterial burden in different organs, enhanced pathogen clearance and increased host survival. Additionally, the sustained innate activated IFNγ production could be attributed to iNOS-mediated signaling in Δ chiA mutant infected mice [ 53 ]. Bhat et al .…”
Section: Discussionmentioning
confidence: 99%
“…For instance, low proliferative capacity is a key character of T cell dysfunction [ 54 ], and cell proliferation is one of the most used assays to evaluate the biological functions of PD-1/PD-L1 inhibitors. In addition, the detection of IL-2 and IFN-γ are also widely used in the functional assay as IL-2 and IFN-γ are essential for T cell proliferation and activity, respectively [ 107 , 108 ]. Furthermore, signaling proteins involved in the PD-1/PD-L1 axis-mediated signaling transductions can be investigated to evaluate the biological effects of PD-1/PD-L1 inhibitors.…”
Section: Current Methodologies For the Development Of Pd-1/pd-l1 Inhibitorsmentioning
confidence: 99%